Methodological Guidelines for the Individual Educational Program for a Student with Special Educational Needs - Fidosieva, Hristina (Педагогически форум, 2025)
This article examines methodological guidelines for developing an Individual Educational Program (IEP) for students with Special Educational Needs (SEN). The IEP is a key tool for ensuring inclusive and high-quality education, addressing the unique needs, abilities, and interests of students. The theoretical foundations of the IEP are analyzed, highlighting the importance of individualization, realistic goal-setting, collaboration, and flexibility in the educational process. Key principles for designing an effective IEP are presented, along with the stages and participants involved in its development and implementation. The article emphasizes potential challenges that may arise during the IEP’s creation and application and offers practical solutions to address them. The study underscores that the IEP is an essential component of modern inclusive education systems, integrating theoretical and practical dimensions to achieve active participation and holistic development for students with Special Educational Needs.